ChemInform Abstract: Cu(I)‐Catalyzed Domino Reaction of 3‐Cyclopropylideneprop‐2‐en‐1‐ones. Issue 30 (4th July 2013) - Miao, Maozhong; Cao, Jian; Zhang, Jingjing; Huang, Xian; Wu, Luling
Abstract An interesting new route to benzofuranone derivatives with one highly strained three‐membered ring and one four‐membered ring is reported.